Intervención humanitaria en Estados fallidos: el caso de monusco en la República Democrática del Congo - Vázquez Cortés, Nadia Concepción (El Colegio de México A.C., 2014)
At the end of World War II, international organizations played a leading role in the configuration of the new world order. In this context, the un positioned itself as one of the most influential international actors, above all through its peace missions.However, in many cases these missions have not been successful, leading many scholars to question the work of the organization. The case of the Democratic Republic of Congo is a clear example of the failure of humanitarian intervention; despite the 14-year presence of the un, the country remains at the top of the ranking of failed states.